2023
DOI: 10.1002/adom.202302383
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Broadband NIR Emission in Fe3+‐Activated ALaBB′O6 (A = Ba, Sr, Ca; B–B′ = Li–Te, Mg–Sb) Phosphors via Multi‐Site Ionic Co‐Substitutions

Shikun Su,
Chen Hu,
Shaolei Ding
et al.

Abstract: Phosphor‐converted near‐infrared (NIR) LEDs are becoming increasingly demanded as miniature, portability, and broad emission spectrum. In this work, a class of Fe3+‐activated double perovskite structured is reported ALaBB′O6 (A = Ba, Sr, Ca; B–B′ = Li–Te, Mg–Sb) phosphors. Through the co‐substitution strategy at the A‐site and B‐B' sites, the emission spectral intensity and position of Fe3+ ions can be tuned. Finally, by utilizing Ca2+ at the A‐site and Mg–Sb co‐substitution for Li–Te, long‐wave NIR emission c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…But the lattice occupancy of Cr 4+ in the matrix not only needs to consider the coordination environment but also the radius and valence state of the substituted ions. The radius difference ratio induced by ion replacement can be expressed by the following formula: D r = R s false( CN false) R d false( CN false) R s false( CN false) × 100 where D r represents the percentage of radius difference, R s and R d represent the radius of the substituted center ion and the radius of the doped ion, respectively, and CN represents the coordination number. Table summarizes ion radius and valence states in ABO 2 and the calculated percentage of radius difference caused by Cr 4+ substitution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…But the lattice occupancy of Cr 4+ in the matrix not only needs to consider the coordination environment but also the radius and valence state of the substituted ions. The radius difference ratio induced by ion replacement can be expressed by the following formula: D r = R s false( CN false) R d false( CN false) R s false( CN false) × 100 where D r represents the percentage of radius difference, R s and R d represent the radius of the substituted center ion and the radius of the doped ion, respectively, and CN represents the coordination number. Table summarizes ion radius and valence states in ABO 2 and the calculated percentage of radius difference caused by Cr 4+ substitution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In previous studies, it has been found that introducing Cr 3+ , 14 Fe 3+ , 15,16 Ni 2+ , 17,18 Bi 2+ , 19,20 Eu 2+ , 21,22 and Yb 3+ 23,24 ions in inorganic materials can produce near-infrared photoluminescence. Among these potential candidates, Cr 3+ has become a popular far-red emitting activator applied in plant growth, as it can not only be excited efficiently by blue-violet light but also its emission can be controlled by the crystal field strength.…”
Section: Introductionmentioning
confidence: 99%